Religion, Nationalism, and Political Evolution: A Historical Analysis of Identity and Security in Bangladesh - Mahbub, Ehsanul (IIUM Journal of Religion and Civilisational Studies, 2025)
This study examines the contested evolution of nationalism and political identity in Bangladesh, focusing on the interplay of religion, politics, and security since 1971. The central issue revolves around tension between secular Bengali nationalism and Bangladeshi nationalism, complicating efforts to establish a cohesive national identity. Employing a historical and conceptual analysis, this study traces these ideological shifts from their colonial-era roots to their contemporary manifestations. The findings reveal that while secular Bengali nationalism sought cultural unity through linguistic and historical heritage, Bangladeshi nationalism introduced inclusivity by integrating broader cultural and religious identities. The study concludes that these ideological contestations have profound implications for Bangladesh’s political stability, societal cohesion, and national security.